1994
DOI: 10.1007/bf01972894
|View full text |Cite
|
Sign up to set email alerts
|

Elevated arterial blood pressure is associated with peri-intraventricular haemorrhage

Abstract: Our results suggest that elevated diastolic, mean and systolic blood pressure are significantly associated with peri-intraventricular haemorrhage in preterm newborn infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
1
16
2
3
Order By: Relevance
“…This process produced 16 article,s which appeared likely to provide information about the relationship between BP and ultrasound brain abnormalities in the neonatal period. 8,13,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] These articles are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This process produced 16 article,s which appeared likely to provide information about the relationship between BP and ultrasound brain abnormalities in the neonatal period. 8,13,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] These articles are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Gronlund et al 16 sugerem que aumentos nas pressões sistólica, diastólica e média estão significativamente associados ao desenvolvimento da HPIV em recém-nascidos pré-termo. Tsuji et al 17 mostraram como o aumento da pressão arterial média estava associado às variações da oxigenação intravascular cerebral em prematuros criticamente doentes.…”
Section: Discussão E Conclusãounclassified
“…Not surprisingly, this relationship has resulted in conflicting evidence implicating high, low and fluctuant arterial blood pressure (ABP) as contributors to neonatal brain injury. [1][2][3][4][5][6][7][8] Recently, the preponderance of this data has shown that low ABP is associated with neurologic injury, but optimal hemodynamic management of the premature infant remains elusive.…”
Section: Introductionmentioning
confidence: 99%